Hang on, Hopper! - Pfister, Marcus (New York : North-South Books, 1997)
Hopper the Arctic hare attempts a shortcut across a river even though he cannot swim.
Translation of: Hoppel lernt schwimmen.
3.0
K-3
Keywords: Hares -- Fiction; Rabbits -- Fiction; Rabbits -- Fiction